The Effectiveness of Self Esteem Psychoeducation to Reduce Academic Procrastination in Vocational High School Students: Efektivitas Psikoedukasi Self Esteem untuk Menurunkan Prokrastinasi Akademik pada Siswa SMK - Royhan, Muhammad Dzaky; Maryam, Effy Wardati (UMSIDA Preprints Server, 2025)
This study aims to examine the effectiveness of psychoeducation focused on enhancing self-esteem in reducing academic procrastination among students at SMK Antarctica 1 Sidoarjo. Using a quantitative pre-experimental design with a one-group pre-test post-test model, the study involved 40 randomly selected 11th-grade TKR students. The instrument used was an academic procrastination questionnaire, and data were analyzed using a paired sample t-test with the IBM JASP Version 0.18.3.0 application.